A clinicopathological study to determine age specific prevalence rate of benign breast lumps - Hussian, Noor Hassan; Mohanta, Pradip Kumar; Biswas, Subikash; Besra, Siddhabrata; Pal, Sabuj; Roy, Debasish (International Surgery Journal, 2019)
Background: The pathogenesis involves disturbance in the breast physiology extending from an extreme normality to well defined disease processes. The clinician must provide a degree of diagnostic accuracy while at same time ensuring that an excessive biopsy rate is prevented. The aim of this study was to evaluate the benign breast lumps in different age groups and to determine the prevalence of benign breast lumps among the breast symptomatic. Methods: This clinico-pathological cross sectional study was conducted with a sample size of 100. The study was conducted during the period from July 2018 to June 2019 which included all patients presenting with benign breast lump during the study period. Results: Out of 100 studied cases of benign breast diseases, the most common benign breast tumor found as fibro adenoma and majority of the fibro adenoma found in the 2nd and 3rd decade of life. Right breast and upper outer quadrant were most commonly affected. Majority of benign breast lesions presented with painless lump in the breast and most of them were from rural background. Majority of benign Breast lumps (45%) cases were found in the age group of 21-30 years. Majority of the patients (60%) attain menarche between ages 13-15 years. Majority of cases (55%) were belonged to lower socio economic status. Conclusions: Our study indicates that FNAC is diagnostically more accurate, safe, cost effective and OPD procedure, however when FNAC was inconclusive, biopsy is the best choice for breast tumors.